IDENTIFYING GAPS AND NEEDS IN ENGLISH TEACHINGPRACTICES FOR EFFECTIVE IMPLEMENTATION OF THE KURIKULUM MERDEKA AT SMASTUNAS BHAKTI PONTIANAK - Calista, Claudia; Hafis, Malikul; Sahrawi (Journal of Language Teaching Lingustics and Literature, 2025)
This study aims to identify gaps and needs in English language teaching practices to support a more effective implementation of Merdeka Curriculum at SMAS Tunas Bhakti Pontianak, a small private school with limited resources. Merdeka Curriculum emphasizes differentiated learning, character strengthening through the Pancasila Student Profile, and project-based learning approaches. However, in its implementation, various obstacles emerged, such as teachers' limited understanding of new learning approaches, low student engagement, and the dominance of conventional learning methods. In addition, the lack of infrastructure such as digital devices, collaborative spaces, and varied learning media is also an additional obstacle. This study also found that teachers need continuous and specific professional training related to teaching module development, differentiated learning design, and PjBL implementation. The results of this study contribute to improving teacher capacity and school readiness in implementing Merdeka Curriculum, and provide input for stakeholders to design mentoring programs that are appropriate to the conditions in the field.